(untitled) (Fiep Bulletin - online, 2015)
Summary the modern organizations are facing surrounding extremely dynamic, provoking radical alterations in the way to be managed. Thus, with the advent and the perfectioning of the organizations theories, the knowledge became the more important economic factor in the competitive environment of the organizations. Treating more specifically to the sportive area, in Brazil the clubs that more adopted the paradigms of enterprise organization had been the Teamses of Soccer, perhaps, for if dealing with the sport most popular of the country. This study it has as objective to investigate, inside of a Club of national Soccer, if it exists the development of teams of high performance and which had been the taken procedures to arrive itself at this. The methodology of the research used in this study is of the qualitative and exploratory type, of the point of view of its nature that has as characteristic an applied research. For the collection of data the half-structuralized interview was used as instrument. The analysis was established in the procedure of the content analysis. The conclusions of the research had pointed that the results reached in the activity end of the club, the sportive context, using the sharing of the knowledge through a disciplined model of management are an example of that the management of the knowledge lead to the evolution of the organization. In the case of the Athletical club Paranaense, the performance of the directive team demonstrated, through the management of the knowledge, to establish clear objectives of performance, defined and accomplished the goals based on performance, found the work boarding integrating abilities and, mainly, it developed objective ways to implant disciplines it conscientious of that all are responsible for the presented results.